A Negative Correlation Between MEFV Mutations and Allergic Diseases - Malik Ejder Yıldırım; Hande Küçük Kurtulgan; Hasan Kılıçgün; Fatma Duksal (Galenos Yayinevi, 2022)
Aim:Atopy is associated with a genetic predisposition to develop allergic diseases such as allergic rhinitis, asthma, and atopic dermatitis. In this study, we aimed to compare the prevalence of Familial Mediterranean Fever (FMF) mutations in asthma and allergic rhinitis patients with controls in the pediatric population and to analyse the positive or negative effect of MEFV mutations in the development of atopy.Materials and Methods:For the detection of FMF mutations, 88 pediatric patients (51 allergic asthma, 17 allergic rhinitis and 20 both asthma and allergic rhinitis cases) and 92 controls were included in our study. Total genomic DNA was extracted from peripheral blood samples using DNA isolation kit. Then, the patient and control groups were screened for MEFV gene mutations by Reverse Hybridization procedure (Strip Assay).Results:There were 9 carriers (heterozygous mutation) in the patient group. The control group had 21 carriers and 1 individual with a compound heterozygous mutation. It was not detected any homozygous mutation in both two groups. The number of individuals with mutation was statistically higher in the control group than in the patients of asthma and allergic rhinitis (p=0.015) and the mutation number (allelic frequency) in the control group was also higher than in the patients (p=0.014).Conclusion:We suggest that FMF mutations are less frequent in allergic rhinitis and asthma cases than in the normal population. Asthma and allergic rhinitis may be more common in individuals without FMF mutation. It can be thought that MEFV gene mutations are effective to prevent allergic reactions on the basis of T helper 2 (Th2) suppression.